The Implementation of Creative Problem-Solving Model In Improving Creative Thinking, Problem-Solving, and Self-Regulated Learning Skills In Literature Learning For Grade XI Students of Saint Ursula High School - Agnes Cristin Ari Nurlia (Jurnal Indonesia Sosial Sains, 2024)
Creative thinking, problem-solving, and self-regulated learning skills are essential 21st-century skills that need to be developed. However, not many students have mastered these three skills. This research aims to determine the results of implementing the Creative Problem Solving (CPS) learning model to enhance these skills in English literature class for Grade XI at Santa Ursula High School in Jakarta. The research was conducted using the classroom action research (CAR) method, which consisted of three cycles. Each cycle involved the planning, observation, action, and reflection phases. A pre-test was conducted before starting each cycle, followed by a post-test after completing the cycle. The research subjects consisted of 32 students, and the assessment instrument used a scoring rubric. The results showed that there was an increase in the average value of creative thinking skills, problem-solving, and self-regulated learning in each cycle. From these results, it can be concluded that the CPS learning model can improve creative thinking, problem-solving, and self-regulated learning skills in English literature classes for Grade XI students at Saint Ursula High School Jakarta.